2000
DOI: 10.1088/0963-6625/9/4/306
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in scientific knowledge and attitudes toward science: a comparative study of four Anglo-American nations

Abstract: Despite a lack of empirical verification, research analysts and populist commentators have long assumed that a key factor in explaining anti-scientific attitudes among women is their greater disinterest and ignorance of scientific developments. Using nationally representative Anglo-American data from the 1993 International Social Survey Programme (ISSP) Environment Survey, the results of this analysis question that assumption. Women in the United States, Canada, Great Britain and New Zealand are indeed less kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 12 publications
4
83
1
4
Order By: Relevance
“…Others have shown that perceptions of technological risks are related to certain types of worldview (Slovic and Peters 1998) While these criticisms are undoubtedly in many ways valid, they do not, in our view, sufficiently problematise the deficit model to justify scrapping it entirely. Indeed, we find it puzzling that many scholars utilising survey research methods that consistently uncover associations between knowledge of and attitudes towards science, despite controlling for a range of other important characteristics such as age, education and social class, often choose to ignore this finding and instead emphasise the other factors that are also influential in the formation of attitudes (Hayes and Tariq 2000, Hayes and Tariq 2001, Sturgis and Allum 2001. It is quite clear that culture, economic factors, social and political values and worldviews are all important in determining the public's attitude towards science.…”
Section: The Deficit Model and Its Criticsmentioning
confidence: 88%
“…Others have shown that perceptions of technological risks are related to certain types of worldview (Slovic and Peters 1998) While these criticisms are undoubtedly in many ways valid, they do not, in our view, sufficiently problematise the deficit model to justify scrapping it entirely. Indeed, we find it puzzling that many scholars utilising survey research methods that consistently uncover associations between knowledge of and attitudes towards science, despite controlling for a range of other important characteristics such as age, education and social class, often choose to ignore this finding and instead emphasise the other factors that are also influential in the formation of attitudes (Hayes and Tariq 2000, Hayes and Tariq 2001, Sturgis and Allum 2001. It is quite clear that culture, economic factors, social and political values and worldviews are all important in determining the public's attitude towards science.…”
Section: The Deficit Model and Its Criticsmentioning
confidence: 88%
“…Other studies have used these or similar questions to measure "general attitudes toward science" (Bauer, Durant and Evans, 1994, p. 174;Hayes & Tariq, 2000). I parse the meaning of each of these questions more closely and consider them to measure different types of faith in science.…”
Section: Dependent Variables: Faith In Science Questionsmentioning
confidence: 99%
“…Subsequent factor analyses on the six variables all produced single-factor solutions for 1993, 2000, and 2010. Interestingly, as Hayes & Tariq (2000) also points out, the negative wording of statements such as these which are used to gauge public attitude toward organized science and its influence on the natural world avoids acquiescence response bias, or the tendency of respondents simply to agree with whatever the interviewer says (p.438).…”
Section: Environmental Attitudes In the Philippinesmentioning
confidence: 99%
“…Willingness and Dangers were the only predictors of Negativity attitudes initially found to be consistently significant in all three datasets, along with these other significant predictors considered for the analysis were: The respondent's selfefficacy items stating difficulty of helping the environment (EfficFatalism) and doing what is right even at the cost of money and time (EfficAltruism); Locus of control for environmental protection(State intervention); and Postmaterialism. These substantial variables are then combined with demographic control variables frequently utilized in myriad studies utilizing ISSP surveys such as: Age, gender, urban or rural settings, education, marital status (Hadler & Haller, 2011;Hayes & Tariq, 2000;Franzen & Vogl, 2013;Marquart-Pyatt, 2012), along with self-assessed subjective socio-economic class within the Philippines (Sabio 2012) in an ordinary least-squares regression similar to the approach of Aoyagi-Usui et al (2003) in order to explore the relationship to environmental attitudes ( Table 4). The final model found Dangers and EfficFatalism to be significant in all datasets.…”
Section: Relationship Between Attitudes and Other Substantial Variablesmentioning
confidence: 99%